Respon Tanaman Selada (Lactuca sativa) terhadap pemberian Pupuk Hayati dengan Berbagai Agen Hayati - Yelianti, Upik (Universitas Jambi, 2011)
This research aims to study the response of lettuce on the application of a variety of biological fertilizers and biological agents. This research was conducted at the Greenhouse School of Agriculture, University of Andalas Padang, between April and September 2008. This study using Completely Randomized Design with factorial of two factors. Factor I is type of biofertilizer (a1: TKTH, a2: JPTH, a3: SKCT, and a4: ATCT) and factor II is the type of biological agent (b1: FMA, b2: Pf, b3: Bb, and b4: FMA + Bb + Pf). Observation parameters include: plant height, root length, and fresh weight of lettuce. Observations show that there is interaction between biological fertilizers with different types of biological agents on the growth of lettuce. The highest plant (29.33 cm) was observed on the treatment of biological fertilizers SKCT with a mixture of biological agents (FMA + Pf + Bb). The longest lettuce roots was obtained on the treatment of biological fertilizers SKCT with biological agents Bb, however the treatment did not differ significantly from AMF + PF + BB (19.67 versus 19:00 cm). While the heaviest of fresh lettuce (99.68 g / plant) is obtained on the treatment of ATCT biological fertilizers combined with FMA biological agent.